Analisis Komunikasi Partisipasi dalam Penyelenggaraan Program Perbaikan Gizi Masyarakat (Studi Kasus pada Kelompok Gizi Masyarakat Pulokerto Kota Palembang) - Ali Alamsyah Kusumadinata; Sarwititi Sarwoprasodjo; Ninuk Purnaningsih (Institut Pertanian Bogor, 2012)
ABSTRACT Nutrition interventionthrough community empowerment program aims to empower improve people's nutrition. this research was done in the district of Pulokerto, Palembang city. The aims of this research were (1) to analyze the meaning of the personal factor in nutrition improvement program, (2) to analyze the group dynamics that occur in nutrition improvement program, (3) to analyze the participatory communication that takes place in the nutrition program. This research was conducted with qualitative methods used the instrumental case study approach. Data was collected by interviewing the participant involved, participating observation and documentation. The results showed that (1) the influence of personal factors in the empowerment program to improve nutrition and motivational factors, affected the perception of community involvement in the program. (2) Factors affecting the dynamics of group empowerment program of activities to improve nutrition, looked at cohesion, leadership and role within the group. (3) The communication mode of participation that occur using monologues and dialogues in the success of nutrition improvement program on community empowerment. Keywords: participatory communication, dynamic group, personal factors